Chinese computational linguistics and natural language processing based on naturally annotated big data : 14th China National Conference, CCL 2015, and third International Symposium, NLP-NABD 2015, Guangzhou, China, November 13-14, 2015. Proceedings /: 14th China National Conference, CCL 2015, and third International Symposium, NLP-NABD 2015, Guangzhou, China, November 13-14, 2015. Proceedings. (2015) - Unknown
No abstract available